New Methods of National Ideology in the 21st Century in Strengthening the National Statehood Mindset (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
National ideology is the spiritual basis of the nation, the unity of the people and the existence of the state. A nation has its own history, culture, customs, traditions and goals for the future. Each independent state, seeking to colonize the intellectual unity of its people, gained internal power, external influence, monopoly, and authority. In this sense, national ideology serves to preserve national identity and promote nationalism in a global context.